Method of stochastic orthogonal expansion in the theory of nonlinear radio systems - Бедный, Н. С.; Бойко, И. Ф. (Proceedings of National Aviation University (archive), 1999)
The opportunity of practical use of a method of stochastic orthogonal expansion is examined for the solution of tasks of the analysis of nonlinear systems under influence of linear random processes